EXPLORING EARLY CHILDHOOD EDUCATION ENGLISH TEACHERS' SELF-VIEW ON TEACHER LEADERSHIP THROUGH THEIR LISTENING CLASS - Wijayanti, Anita; Margana, Margana; Sukarno, Sukarno (Jurnal Suluh Pendidikan, 2025)
ECE) English teachers, focusing on its relationship with leadership perspectives and practices within the context of their listening classes. The study employed a mixed-methods research design and used a questionnaire as its instrument. questionnaire, in which its high reliability was guaranteed by the use of (Cronbach's Alpha = 0.930) and a validity test on its instruments, which confirmed that all items were valid for hypothesis testing. A group of 50 ECE English teachers offered their participation, and data was collected via a questionnaire. Descriptive analysis revealed positive feedback from respondents, concluding the significance of fostering listening skills in educational settings. The appropriateness of the data for regression analysis was ensured by employing classic assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation. Multiple linear regression analysis revealed a significant positive influence of both Teacher Leadership Perspective (β = 0.496) and Teacher Leadership Practice (β = 0.433) on Teacher Leadership Identity, with the model explaining 74.9% of the variance in the dependent variable. Findings stated the importance of understanding the interconnections among these constructs to enhance teacher leadership in educational contexts. It is recommended that educators facilitate programs focused on leadership and listening skills and establish professional learning communities to improve listening effectively. This study’s limitation is its reliance primarily on quantitative and qualitative data. Future research may benefit from a cross-method approach to avoid reliance on a single form of data.